New records of the rare grasshopper species Bradyporus multituberculatus multituberculatus (Fischer von Waldheim, 1833) (Orthoptera: Tettigoniidae) in the Chechen Republic, Russia - Т.А. Avtaeva; Sh.А. Kushalieva (Кавказский энтомологический бюллетень, 2017)
Data on new present-day findings of a rare species of orthopteroid insects Bradyporus multituberculatus multituberculatus (Fischer von Waldheim, 1833) in the Chechen Republic are presented. Several specimens of B.  multituberculatus multituberculatus were found in the village of Meken-Yurt of the Nadterechny district and in the village of Terskoe of the Grozny district. This species was first found in the republic in the 1950s and since that time it has been considered to be extinct. In 1990 B.  multituberculatus multituberculatus was identified at the border of Dagestan and Chechnya, and in 2012 several populations were found in the Kabardino-Balkarian Republic. Findings of the species populations in the republics of the North Caucasus disestablished the opinion of many Russian and foreign colleagues considering this species to be extinct. The global range of nominative subspecies includes the steppes of the Ukraine and the south of the European part of Russia. By now the Eastern Pre-Caucasian Region is the only territory in the world where B. multituberculatus multituberculatus is preserved. All three findings were made on river terraces of the Nadterechnaya Valley (the terrace above the Terek floodplain) in three different biotypes: 1) flood-plain forest with tree and shrubbery vegetation; 2)  the region above flood plains with meadow-steppe vegetation; 3)  the region of the steppe of the third terrace above flood-plain with the dissected relief. All specimens were registered in July of 2015. The disastrous decrease in the population and occurrence of the species within this region is caused by the economic activities, primarily by ploughing of virgin steppes. In order to preserve the biodiversity of the Chechen Republic steppes, it is necessary to urgently place the habitats of Bradyporus under protection and introduce a total ban on any economic activity, especially during the active period of larvae and imago (the first half of summer). We propose not to change the status of B. multituberculatus multituberculatus in the European Red List of Orthoptera (from “Endangered” to “Critically Endangered”) considering the information provided above.